IMPLEMENTASI VENTILATOR BUNDLE DAN RISIKO KEJADIAN INFEKSI NOSOKOMIAL PNEUMONIA DI RUANG PERAWATAN INTENSIF RUMAH SAKIT SURAKARTA - Rudy Suryo Handoyo; Iwan Dwiprahasto; Trisari Lestari (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: Ventilator-associated pneumonia (VAP) inventilator assisted breathing patients is one of the mainconcerns in intensive care unit (ICU) because of its relation withhigh incidence and mortality rate. National infection surveillancein France found 12.4% of intubated patients during go infectedwith VAP, with mortality rate of 40-50%. Pneumonia could beprevented by implementing the right precaution, investigationsshow that with good management, VAP could be reduced until70%. Methods: Quantitative study using observational analysis withcohort design. Data collected by observing compliance ofventilator-bundle in adult ICU with checklist. Implementation ofventilator-bundle could be observed directly and by checkingpatient's hemodynamic record. Ventilator-bundle consist ofhand hygiene, oral care with antiseptic, patient's body positionat ≥30° angle, sedation vacation, and weaning assessment,peptic ulcer prophylaxis, and prevention of deep veinthrombosis (DVT). This study use CPIS (clinical pulmonaryinfection score) to diagnose pneumonia. Results: Ventilator-bundle compliance rate are recorded on82.9% and VAP on 11.1%, or 26.7 per 1000 ventilator days.Compliance with the ventilator bundle has no relationship withthe incidence of VAP. By using the odds ratio of noncompliancewith peptic ulcer prophylaxis has 8,5x risk of VAP (95% CI: 1.164to 62.094). This study proves the existence of the patients'factors associated with VAP which are duration of ventilationand incidence of spontaneous ETT pulling. Installation ofventilator for more than 5 days has 36 times greater risk of VAP(95% CI: 3.193 to 405.897). Spontaneous ETT pulling has 26times greater risk of VAP (95% CI: 1.796 to 376.303). between ventilatorbundle compliance with VAP incidence. Thisresult caused by the limited subjects involves. Sample size ofthe study was limited because of the short duration of the study.